Hubungan Sikap Kerja dengan Keluhan Muskuloskeletal Pada Penjahit Konveksi - Amlina, Yanni Rizkia (Universitas Aufa Royhan, 2022)
Musculoskeletal disorders are one of the occupational diseases that are often felt by workers due to various factors, one of which is work attitude. This study aims to determine the relationship between work attitude and musculoskeletal disorders in convection tailors in Sukajadi District and Pekanbaru City District, Pekanbaru City. This study used a descriptive correlational design with a cross sectional approach. The research sample amounted to 45 respondents with sampling using total sampling technique. The analysis used is bivariate analysis using chi-square test. The majority of respondents are adults aged 26-45 years (46.7%), male (64.4%), having a work duration of >8 hours (53.3%) and having worked >5 years (73.3%). The majority of respondents, namely 43 respondents (95.6%) worked with a moderate risk work attitude and 39 respondents (86.7%) experienced moderate level of musculoskeletal disorders. The results of the fisher exact alternative test between work attitudes and musculoskeletal disorders, obtained p value = 0.044 < (0.05). There is a relationship between work attitude and musculoskeletal disorders in convection tailors.